Pengaruh Pengetahuan Kesehatan Gigi dan Mulut terhadap Keterampilan Menyikat Gigi Pada Siswa SDN 17 Kendari - Afdilla, Nia; Farida Jelita, Nurul (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2024)
Dental and oral health is part of physical health as the the main beginning to overall body health. Knowledge is the result of human curiosity activities through certain methods and tools, the impact of not brushing teeth will cause plaque and dental caries in children, and food residue can still be left between the teeth which can become a breeding ground for bacteria and become the trigger for various kinds of dental problems, one of which is caries in children, which causes tooth decay. The aim is to determine the effect of using animated videos in improving dental health knowledge and tooth brushing skills. The type of research used is quantitative research, using a pre-test and post-test group design. The sampling technique was purpositive sampling as many as 32 students. The results of the Wilcoxon test analysis in this study showed that there was a significant influence on dental and oral health knowledge (p>0.001), Paired Sample T-Test analysis test on students' toothbrushing skills (p>0.001). The conclusion is that there is a significant change in increasing knowledge and skills before and after counseling was held using the animated video method for students at SDN 17 Kendari.